Analisis Upaya Guru dalam Pembentukan Karakter Siswa di Sekolah Menengah Pertama - Sufiani, Sufiani (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2024)
This research aims to describe teachers' efforts in forming student character at a junior high school at Konawe Selatan, Southeast Sulawesi, Indonesia. Teachers not only integrate various teaching competencies, but are also required to play various roles that lead to the formation of student character at the school. The subjects in this research were school principals, teachers and students. Data collection techniques in this research are observation, interviews and documentation. The results of the research show that the teacher's efforts in forming student character include habituation, example, enforcing discipline, internalization and integrity. Meanwhile, the character formation of students includes religious values, honesty, tolerance, discipline, creativity, love of reading, care for the environment and responsibility.